Analisis Pemahaman Sertifikasi Halal pada Usaha Mikro Kecil dan Menengah (UMKM) - Aisyah, Dara Istia; Nurmalia, Fidhya; Nur Azizah, Nisrina Athiyyah; Marlina, Lina (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2023)
This research aims to analyze the understanding of halal certification in micro, small and medium enterprises (MSMEs). This research was conducted using a qualitative descriptive approach. Data collection was carried out using observation, interviews and documentation techniques from related sources. Respondents were 15 MSMEs by distributing questionnaires directly. Of the total number of respondents, 33.3% or 5 people understood halal certification and 66.7% or 10 people still did not understand. The results of this research show that understanding of halal certification in Ceungceum Village is still relatively low due to the lack of outreach activities. The government's role is needed to increase understanding of MSMEs by organizing outreach activities and assistance to make it easier to obtain halal certification in the village.